Reducing the delay in eligible couple registration through networking with marriage registrars - AP de Silva; S Jayasinghe; RMSK Ratnayake (College of Community Physicians of Sri Lanka, 2011)
Introduction: The newly married couples are rarely encountered by the Medical Officer of Health (MOH) and there is a de-lay in registering them in the Eligible Couple Register (ECR). A new service model was developed with marriage registrars for newly married. Objective: To describe the delay in eligible couple registration before and after networking with marriage registrars (MR) and to describe the detected pre-pregnancy risk factors through this newly implemented model. Methods: A network was established with the MR to receive information of newly married in the Arachchikattuwa MOH area. Delay in eligible couple registration before and after the implementation of the new model was assessed using data from 06 January 2004 to 12 January 2006. Results: The mean delay in eligible couples registration before and after intervention were 518.9 days and 46.5 days respectively (p=0.001). Registered in the ECR on the same day or after pregnancy registration before and after intervention were 133 (71.1%) and 16 (50%) respectively (p<0.018). The MOH had seen 52 newly married couples during the study period. The number of teenage pregnancies was 14 (26.9%). There were 17 (32.7%) females with a BMI, <18.5kg/m2 and four (7.7%) were treated for malaria. Prevalence of each, consanguinity, short stature and high systolic blood pressure was 5.8% (n=3). Two (3.8%) had failed to obtain rubella vaccine. Rheumatic heart disease and anaemia were detected in one female (1.9%) each. Conclusion: Linking up with marriage registrars reduces the delay in eligible couple registration significantly. Through provision of services by MOH to newly married couples selected pre-pregnancy risk factors can be identified and addressed. It also provides an opportunity for provision of pre-pregnancy care. Key Words Newly married; pre-pregnancy risk factors; new service model; marriage registrars DOI: 10.4038/jccpsl.v13i2.2966 Journal of the College of Community Physicians of Sri Lanka Vol.13(2) 2008 29-33